Effects of occupational exposure to noise and dust on blood pressure in Chinese industrial workers - Jingfeng Lin; Hufei Wang; Fen Yan; Kefu Tang; Huang Zhu; Zuquan Weng; Kejian Wang (Clinical and Experimental Hypertension, 2018)
Along with the rapid development of economy and urbanization, noise and air pollution are becoming major occupational health hazards in the process of industrial production. In this study, we collected data from 7293 industrial workers in China. The association between occupational exposure of noise and dust and blood pressure was investigated. Controlling for demographic variables, including sex, age, and length of service, a stepwise regression model with backward elimination was constructed. The results showed that both noise and dust decreased the level of systolic blood pressure (p < 0.001). This finding prompted the manufacturing industry to reduce noise and dust hazards and protect the occupational health of workers. Prospective studies in different populations are still required to verify the net contribution of noise and dust to the decrease in blood pressure.